Daylighting pedagogy: How can new pedagogic approaches for daylighting enhance opportunities for engaging with daylight in spatial design education? - Treacy, Gillian Avril (The University of Edinburgh, 2021)
Experience of spatial design practice (architecture, interior and lighting design) and spatial design teaching in the UK has highlighted a growing dichotomy in the field of architectural daylighting design. A separation is apparent between either quantitative or qualitative daylighting design agendas, growing out of, and characterising divergent Communities of Practice. This issue is of critical concern as we consider the emergent challenges facing spatial designers. Spatial designers will be expected to contribute to building occupants’ health and well-being through the aesthetic and functional requirements of the spatial design, consistently meeting building energy targets and integrating new technological advances into holistically evaluated spatial design proposals. Daylighting plays an important role in meeting these challenges. Although spatial designers attribute great value to daylit architectural spaces, this study demonstrates that for many architects and interior designers, their use of existing daylighting threshold concepts, lighting tools, definitions and metrics is limited, indicating problematic underlying ontological and pedagogical perspectives. As a consequence of this, the design aims and occupants’ spatial environments are compromised. This thesis therefore asks: • How can new pedagogical methodologies challenge current ontologies in relation to daylight in spatial design contexts? • How can these methodologies benefit future spatial design and daylighting agendas? The thesis outlines these dichotomies, drawing on educational and design process theories and studying the ontological agendas for daylighting prevalent within spatial design educational contexts and practice. It identifies new ways of thinking about daylight needed to address and transform this current situation. Pedagogical approaches are proposed, based on ‘threshold concepts’ Cousin (2006), designed to underpin daylighting design decision making and align with familiar ‘designerly ways of knowing’ Cross (2006). The thesis subsequently challenges, proposes and explores a dual-ontological approach for daylighting design exploring heuristic methods to assist future holistic design demands. The study uses recorded task-based workshops to reveal the success of these designed didactics in exposing and supporting relational thinking using selected threshold concepts for daylight. The methods proposed invite simultaneous qualitative and quantitative translational moments through, ‘see’ing, ‘touch’ing and ‘record’ing light. The research concludes that simultaneous engagement with the dual-ontologies for daylight not only encourages relational understanding of the greater spatial environment but broadens a designer’s perspective of daylighting design and the criticality of its place within future holistic spatial design proposals.
Keywords: spatial design teaching; lighting design; daylighting; daylight; educational context